The Portuguese version of Beck Depression Inventory-II (BDI-II): - Campos, Rui C. (2011)
Beck Depression Inventory-II (BDI-II) is one of the most popular and investigated instruments for assessing the severity of depressive symptomatology. The authors developed a Portuguese version of the inventory. This paper presents two studies: one with a college student sample (n = 547) and another with a community sample (n = 200). Reliability, factor structure and validity data were obtained. The Portuguese version presents a good internal consistency, a factor structure very similar to the one obtained by Beck, Steer and Brown (1996) with the original version and presents an adequate convergent validity with the Center for Epidemiologic Studies of Depression Scale. Confirmatory factor analysis provides support for the fit of a two-factor model.